2020
DOI: 10.1186/s12866-020-01821-8
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore sequencing reveals genomic map of CTX-M-type extended-spectrum β-lactamases carried by Escherichia coli strains isolated from blue mussels (Mytilus edulis) in Norway

Abstract: Background: Environmental surveillance of antibiotic resistance can contribute towards better understanding and management of human and environmental health. This study applied a combination of long-read Oxford Nanopore MinION and short-read Illumina MiSeq-based sequencing to obtain closed complete genome sequences of two CTX-M-producing multidrug-resistant Escherichia coli strains isolated from blue mussels (Mytilus edulis) in Norway, in order to understand the potential for mobility of the detected antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 71 publications
0
7
1
Order By: Relevance
“…The overall results from our study are in accordance with previous studies on AMR in bacteria from the Norwegian marine environment, where low prevalence of acquired resistance was found in E. coli and Vibrio spp. [22,60,61]. In the present study, acquired resistance was only found in few K. pneumoniae isolates and in none of the other isolated species.…”
Section: Discussioncontrasting
confidence: 52%
“…The overall results from our study are in accordance with previous studies on AMR in bacteria from the Norwegian marine environment, where low prevalence of acquired resistance was found in E. coli and Vibrio spp. [22,60,61]. In the present study, acquired resistance was only found in few K. pneumoniae isolates and in none of the other isolated species.…”
Section: Discussioncontrasting
confidence: 52%
“…Similarly, many conjugative plasmids, such as IncF, IncI, IncK, and IncHI2, play important roles in the global dissemination of extended-spectrum β-lactamase ( ESBL ) genes, which confers resistance to most β-lactam antimicrobials, especially to third-generation cephalosporins ( Wang et al., 2018b ; Irrgang et al., 2018 ; Furlan et al., 2020 ; Grevskott et al., 2020 ). Studies over the last decade have shown that class A β-lactamases belonging to the CTX-M-type have become the predominant ESBL in many parts of the world, and have spread rapidly among clinical populations of Enterobacterales ( D'Andrea et al., 2013 ; Furlan et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand the genetic context of the mcr-4.3 gene, we determined the complete, closed genome sequence of S. baltica strain 11FHM2 (carrying mcr-4.3 and a novel catB variant), using an Oxford Nanopore MinION instrument, as described previously ( 12 ). The complete genome of strain 11FHM2 was determined to be 5,406,724 bp, with one contig representing a chromosome of 5,068,880 bp and three contigs representing novel plasmids (pSBP1, 194,145 bp; pSBP2_mcr4, 86,727 bp; and pSBP3, 56,972 bp).…”
Section: Observationmentioning
confidence: 99%